Isolation and Characterization of Saraca asoca, Secondary Metabolites by Rhizopus sps Using Various Analytical Techniques, Including FTIR, NMR, and HPLC - Ashwini; Ramachandra, Y.L. Ramachandra (International Journal of Applied Sciences and Biotechnology, 2025)
Ashoka (Saraca asoca) is a conventionally used medicinal plant in India, known for its curative properties. Secondary metabolites, which are the bioactive compounds produced by living organisms, can unveil symbiotic relationships in nature. The present study elucidated that secondary metabolites show the presence of various bioactive compounds, where the Saraca asoca endophyte extract was tested against various bacteria like E. coli, S. aureus, B. subtilis, K. pneumoniae, P. aeruginosa, and P. syringae, which showed the zone of inhibition. The characterization of endophytic extract is used for various analytical techniques, such as FTIR, which is used to detect the presence of functional groups like ketones, Alkenes, Aromatic Compounds, Nitro Compounds, Alkyl and Aryl Halides. HPLC analysis showed the presence of Caffeine, its Ret Time at 3.033, and NMR results showed the Chemical shift at 4.391, an ArOH type of bond present. It was the Phenol, whereas others showed 3.769 and its bond structure is ArNH2, it belongs to Aniline, 2.510 showed the bond structure RC≡C-H, it belongs to Alkynyl. Bioactive compounds are used to synthesize novel drugs. These drugs showed antioxidant and anticancer activity. Int. J. Appl. Sci. Biotechnol. Vol 13(2): 94-99.